THE NEED TO CREATE A MORPHOLOGICAL DICTIONARY OF UZBEK LANGUAGE - Kholiyorov Ural Mengliyevich (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes in detail the formation of a morphological dictionary of the Uzbek language. Compares similarities and differences with morphological dictionaries and grammar dictionaries. World experience, theoretical views and research in the Uzbek language are studied. The work on the first morphological dictionaries is also covered. Suggestions for future work on morphological dictionaries have been developed.